DISTRIBUTION FEATURES OF MEASURED WAVE CHARACTERISTICS IN COASTAL WATERS OF NINH THUAN PROVINCE, VIETNAM - Mau, Le Dinh; Tuan, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2019)
This paper presents the distribution features of wave characteristics based on the continued measurement wave data with interval of 1 hour from January to December 2013 in coastal waters of Ninh Thuan province. The study results show that the dominant wave directions were in East-North-East (ENE), East (E), South-South-East (SSE) and South-East (SE) with occurrence frequency of 36.7%, 20.5%, 18.2% and 11.6% respectively. During North-East (NE) monsoon the dominant wave directions were in ENE and E. During South-West (SW) monsoon the dominant wave directions were in SSE and SE. The remaining directions were rare. The maximum values of wave height (Hmax) was 4.84 m (11/2013), wave period (T) was 10.9 s (11/2013). The occurrence frequency of Hs ≤ 0.5 m was 43.9%, Hs ≈ 0.5–1.0m was 21.9%, Hs ≈ 0.5–1.0 m was 21.9%, Hs ≈ 1.0–2.0 m was 27.3%, Hs > 2.0 m was 6.8% and calm wave condition (Hs ≤ 0.25 m) was 8.1%. The duration and intensity of wave action were dominant in NE monsoon period